Kitten's first full moon - Henkes, Kevin ([New York] : Greenwillow Books, 2004)
When Kitten mistakes the full moon for a bowl of milk, she ends up tired, wet, and hungry trying to reach it.
Keywords: Cats; Animals -- Infancy; Cats; Animals -- Infancy; Moon; Moon